Orientalism discourse reversal in Budi Darma’s Tarom short story - Waluyo, Isnan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This paper aims to examine the short story Tarom by Budi Darma with theoretical knife of orientalism. The method in this study uses descriptive qualitative. The data collection technique uses the close-reading method, while the analysis technique uses the dialectical method. Edward Said’s Orientalism as a formal object and Budi Darma’s short story Tarom published by Kompas newspaper is a material object. The results of study suggest that, first, there is a polarization of ‘West’ and ‘East’ which is represented by the characters in the short story. The West in this case is depicted Germany and the East shown is Japan. Second, it does not only describe the polarization of the West and the East, but also shows the discourse of resistance. Through the depiction of the Tarom character, this short story shows the existence of a Western body with Easten thoughts. Thus, the short story Tarom displays a narrative of reversal of the Orientalism discourse.